A Review on Natural Fibre Reinforced Polymer Composites - Debnath, Sujan; Nguong, C.W.; Lee, S.N.B. (WORLD ACADEMY OF SCIENCE, ENGINEERING AND TECHNOLOGY, 2013)
Renewable natural fibres such as oil palm, flax, andpineapple leaf can be utilized to obtain new high performancepolymer materials. The reuse of waste natural fibres as reinforcementfor polymer is a sustainable option to the environment. However, dueto its high hydroxyl content of cellulose, natural fibres aresusceptible to absorb water that affects the composite mechanicalproperties adversely. Research found that Nano materials such asNano Silica Carbide (n-SiC) and Nano Clay can be added into thepolymer composite to overcome this problem by enhancing itsmechanical properties in wet condition. The addition of Nanomaterial improves the tensile and wear properties, flexural stressstrainbehaviour, fracture toughness, and fracture strength of polymernatural composites in wet and dry conditions.